Early Russian Reception of James Hogg (1830s) - D. N. Zhatkin (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The early Russian reception of the Scottish writer James Hogg (1770—1835), known in his homeland as an interpreter of folk ballads and the author of “The Confession of a Justified Sinner” (1824) — a complex work, which laid the foundation for the theme of multiple personality disorder in English literature is comprehended in the article for the first time. It has been suggested that the first Russian to hear about Hogg and his works was A. I. Turgenev, who visited W. Scott in Abbotsford in August 1828. The materials of the Russian periodicals of the 1830s (“Library for reading”, “Northern Bee”, “Telescope”, “Moscow Observer”), which reported facts about the life and work of Hogg, were comprehended. It is noted that the authors of a number of articles (most of them published without a signature and under kryptonyms) were significant critics and publicists of the era — O. I. Senkovsky, N. A. Polevoy, N. I. Nadezhdin. It was established that in the 1830s, fragments from Hogg’s memoir about the life of W. Scott in Abbotsford “The Domestic Manners and Private Life of Sir Walter Scott” (1834), as well as a fragment from the book “Noctes Ambrosianae” (1802—1835), attributed to Hogg, but in reality a collective work of J. Wilson, J. G. Lockhart, Hogg and W. Maginn were translated into Russian. The analysis of publications about Hogg in periodicals and in the fourteenth volume of the Encyclopedic Lexicon (1838) revealed inaccuracies in the presentation of biographical facts, the tendency of Russian publicists to uncritically perceive the subjective assessments of the Hogg-memoirist, largely due to his desire to emphasize his own literary significance. It is noted that, introducing Hogg as a follower of Burns and a friend of Scott, the authors of articles in Russian periodicals did not pay due attention to Hogg’s creative individuality, the originality of his creative heritage, as a result of which the late period of his literary biography (late 1810s — mid-1830s), associated with the creation of “The Confession of a Justified Sinner” and a number of other significant works, remained unnoticed against the background of early works associated with reliance on folk songs.